CLINICAL SIGNIFICANCE OF ANTIPHOSPHOLIPID ANTIBODIES AND GENE MUTATIONS IN HEMOSTASIS OF CHILDREN WITH SYSTEMIC LUPUS ERYTHEMATOSUS AND JUVENILE DERMATOMYOSITIS - O.A. Solntseva (Педиатрическая фармакология, 2006)
Thrombophilia in children with diffuse connective tissue disorders as systemic lupus erythematosus (SLE) and juvenile dermatomyositis (JDM) could arise from various causes including peripherial blood circulation of antiphospholipid antibodies (APH) and genetic mutations in the system of hemostasis. Thrombosis is a serious and prognostically unfavorable complication that has negative impact on the underlying disease course. The study included 96 children, 65 of them had diagnosed SLE and the other 31 had JDM. The Elisa method was used to detect antiphospholipid antibodies, coagulation method was used to detect lupus anticoagulant (LAC) and antibodies to cardiolipins (anticl), ?2:glycoprotein 1 (anti ? 2 gp 1) and prothrombin (APT). The PCR method (DNA diagnostics) was used to detect DNA mutations as factor resistance to of activated protein c (Leiden) 5,10 methylen tetrahydrofolate reductase (MTHFR) gene polymorphism. The incidence of APL antibodies was registered in 61.5% patients with SLE and in 32.2% of patients with JDM. Ac ligg, anti ?2 gp 1 Igg were clinically significant in thrombotic events in patients with SLE and JDM, and so was LAC in patients with SLE. The prevalence of the hemostasis system mutations is concordant with reported data. Conclusion thrombophilia is frequently associated with APH antibodies or combination of APH antibodies with genetic abnormalities. Sole genetic mutations are salient in patients with JDM.Key words: thrombophilia, systemic lupus erythematosus, juvenile dermatomyositis, antiphospholipid antibodies, lupus anticoagulant, leiden, prothrombin, methylentet rahydrofolate reductase.